2008
DOI: 10.1891/0886-6708.23.1.115
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences and Socioeconomic Status Biases in Judgments About Blame in Date Rape Scenarios

Abstract: Participants (80 men, 80 women) read hypothetical date rape scenarios, wherein the perpetrator's socioeconomic status (bus driver versus doctor) and the victim's level of resistance (verbal versus verbal and physical) were varied, and made judgments about who was at fault and what the consequences should be. In general, men assigned more blame to the victim and less blame to the perpetrator than did women. However, men assigned more blame to the bus driver than to the doctor. Women, on the other hand, assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 0 publications
7
50
0
2
Order By: Relevance
“…It has consistently been found that male observers blame rape victims more than female observers; a finding which is replicated within both traditional (Bell et al, 1994;Furnham & Boston, 1996;Proite et al, 1993) and current research Schneider et al, 2009;Sims et al, 2007). These results relate to situations with female victims (Furnham & Boston, 1996;Sims et al, 2007) as well as male victims Whatley & Riggio, 1993;White & Kurpius, 2002), homosexual (Davies et al, 2001; as well as heterosexual male victims (Burt & DeMello, 2002;Mitchell et al, 1999) and for date rape situations (Black & Gold, 2008;Proite et al, 1993), stranger rape situations (Bell et al, 1994;Davies et al, 2008;Grubb & Harrower, 2009), as well as marital rape situations (Ewoldt et al, 2000). Additionally, male observers tend to be more accepting about rape situations (Talbot, Neill, & Rankin, 2010), and minimize the seriousness of rape scenarios more than female observers (Newcombe, Van den Eynde, Hafner, & Jolly, 2008).…”
Section: Observer Gendersupporting
confidence: 67%
See 1 more Smart Citation
“…It has consistently been found that male observers blame rape victims more than female observers; a finding which is replicated within both traditional (Bell et al, 1994;Furnham & Boston, 1996;Proite et al, 1993) and current research Schneider et al, 2009;Sims et al, 2007). These results relate to situations with female victims (Furnham & Boston, 1996;Sims et al, 2007) as well as male victims Whatley & Riggio, 1993;White & Kurpius, 2002), homosexual (Davies et al, 2001; as well as heterosexual male victims (Burt & DeMello, 2002;Mitchell et al, 1999) and for date rape situations (Black & Gold, 2008;Proite et al, 1993), stranger rape situations (Bell et al, 1994;Davies et al, 2008;Grubb & Harrower, 2009), as well as marital rape situations (Ewoldt et al, 2000). Additionally, male observers tend to be more accepting about rape situations (Talbot, Neill, & Rankin, 2010), and minimize the seriousness of rape scenarios more than female observers (Newcombe, Van den Eynde, Hafner, & Jolly, 2008).…”
Section: Observer Gendersupporting
confidence: 67%
“…One study included time of initial resistance as a variable and found that when initial resistance occurred early in the incident, observers were less likely to think that the rape could have been avoided, which resulted in less blame for the victims, and more blame for the perpetrator (Kopper, 1996). Furthermore, a recent study differentiated various types of resistance, and found that perpetrators were blamed more and held more responsible when victims resisted verbally, compared to both verbally and physically (Black & Gold, 2008).…”
Section: Resistancementioning
confidence: 99%
“…The role of gender, ambivalent sexism, rape myth acceptance, and rape empathy has received much academic attention and all these variables were shown to predict victim blaming. While considering gender differences, most studies showed that men are more likely to blame the victim (e.g., Anderson & Lyons, 2005;Black & Gold, 2008;Durán et al, 2010;Ferrão et al, in press;Gölge et al, 2003;Grubb & Harrower, 2009;Harrison et al, 2008;Schneider et al, 2009;Yamawaki & Tschanz, 2005), but others failed to replicate such findings (e.g., Cohn et al, 2009;Frese et al, 2004;Mandela, 2011;Newcombe et al, 2008;Rye et al, 2006;Strömwall et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, a large number of studies suggests that men are more likely to engage in victim blaming (e.g., Anderson & Lyons, 2005;Bendixen, Henriksen, & Nøstdahl, 2014;Black & Gold, 2008;Durán, Moya, Megías, & Viki, 2010;Ferrão, Gonçalves, Giger, & Parreira, in press;Gölge et al, 2003;Grubb & Harrower, 2009;Harrison, Howerton, Secarea, & Nguyen, 2008;Mitchell, Angelone, Kohlberger, & Hirschman, 2009;Paul, Kehn, Gray, & Salapska-Gelleri, 2014;Schneider, Mori, Lambert, & Wong, 2009;Strömwall, Landström, & Alfredsson, 2014;Yamawaki & Tschanz, 2005). …”
Section: An Overview Of Rape Victim Blaming Observer Gendermentioning
confidence: 99%
“…Participants were asked to associate a target wearing or not wearing eyeglasses with a socioprofessional group. Researchers have reported that information related to the socioprofessional status of a target has influenced observers' judgment of the target (Black & Gold, 2008). As researchers have shown that intelligence is positively correlated with socioprofessional status (Firkowska-Mankiewicz, 2011;Furnham & Cheng, 2013), I hypothesized that a target wearing eyeglasses would be more frequently associated with membership of a high-status socioprofessional group than would the same target when not wearing eyeglasses.…”
mentioning
confidence: 99%